2019
DOI: 10.5114/pjr.2019.90090
|View full text |Cite
|
Sign up to set email alerts
|

How high is the inter-observer reproducibility in the LIRADS reporting system?

Abstract: Purpose: To investigate the reproducibility of LIRADS v2014 and contribute to its widespread use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…23 Prior studies show the reproducibility of LR-3-LR-4 lesions were lower than other categories. 25,26 This study showed the reproducibility level of LR-3-LR-4 remained relatively low even after training. It is indeed unfortunate, considering that the surveillance of these intermediate lesions is more important in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…23 Prior studies show the reproducibility of LR-3-LR-4 lesions were lower than other categories. 25,26 This study showed the reproducibility level of LR-3-LR-4 remained relatively low even after training. It is indeed unfortunate, considering that the surveillance of these intermediate lesions is more important in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 79%
“…Most were single-center studies with 2-10 readers, except for one multicenter study with 113 readers and one dual-center study with 3 readers. [19][20][21][22][23][24][25][26][27][28][29][30] These studies obtained variable reproducibility, ranging from slight compliance to fair compliance for the intermediate categories (LR-2-LR-4), from moderate to perfect for other categories, and from poor to perfect for the overall category. All the studies mentioned above refer to LI-RADS versions 2013-2017, except one that refers to version 2018.…”
mentioning
confidence: 99%
“…4 , 5 Accordingly, there has been increasing reliance upon imaging and radiologists for both early and accurate diagnosis of HCC, using a universal reporting language. 6 …”
Section: Introductionmentioning
confidence: 99%
“…However, some literature has questioned the accuracy and reliability of the LI-RADS risk stratification. 6 , 7 Furthermore, the updated LI-RADS version 2018 has not been widely validated. 8 , 9 , 10 , 11 This retrospective study aims to evaluate the diagnostic accuracy and inter-reader reliability of the current LI-RADS version 2018 lexicon amongst board certified fellowship trained body imaging radiologists as compared with an expert consensus reference standard.…”
Section: Introductionmentioning
confidence: 99%
“…The LI-RADS is a reporting system that is designed to improve and reduces variability and difficulties in the elucidation of imaging findings leading to the most accurate diagnosis, proper staging, and hence, proper treatment [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%